The Effects of Motivation in Student Academic Success - Caldeira, Amélia (2020)
It is common sense, that the student s motivation is a key element within the learning process, and technology is an important tool to motivate students for learning. The modern world is becoming a place where a huge variety of technologies emerges, for example, smartphones, computers, videos.... The use of technology, in the learning process, is a breath of fresh air inside and outside the classroom Videos is a source of material that can play an important role in the students ‘motivation. In this work, we described an initiative where the videos play an important role in the teaching and learning field. , we analyse the student academic success when they experience this kind of project. In this work, we study student results in an academic year where no videos were produced and in an academic year where videos were produced, and we make a comparative study.